Socio-economic impacts of climate change and adaptation actions among smallholder fish farmers in Sub-Saharan Africa - Muthoka, Mavindu; Ouko, Kevin Okoth; Mboya, Jimmy Brian; Ndambuki, Merceline Ndinda; Outa, Nicholas; Ogello, Erick; Obiero, Kevin; Ogola, Robert John; Midamba, Dick Chune; Njogu, Lucy (Wiley, 2024)
Aquaculture is the world's fastest-growing food-producing sector, making it a significant contributor to food and nutrition security for the globally growing human population. Nevertheless, its long-term growth is limited by the effects of climate change. Aquaculture in Sub-Saharan Africa (SSA), which is dominated by small-scale fish farming, is increasingly threatened by climate change, which has a substantial influence on its productivity and scalability. In this context, the present research looks at the socio-economic consequences of climate change on small-scale fish producers in SSA, as well as potential adaptation techniques to the effects of climate change. A clear understanding of these socio-economic repercussions of climate change is critical for developing effective strategies to reduce future impacts and safeguard aquaculture-based livelihoods. Furthermore, understanding the socio-economic consequences of climate change on communities dependent on aquaculture is important for advising policymakers and decision-makers on formulating and implementing policies that sustain aquaculture production amidst the climate change crisis. This article suggests various adaptation strategies to increase resilience to climate change, including diversification of livelihoods and species, use and incorporation of local and indigenous knowledge, shifting to aquaculture species less vulnerable to changing climatic conditions, capacity building through aquaculture insurance schemes, continued fish supply from capture fisheries, and consolidation of equity and human rights concerns. These adaptive methods, when combined, have the potential to enhance outcomes for populations who are more susceptible owing to their unstable socio-economic conditions.